Informe anual 1972 :Programa Nacional de Leguminosas de Grano y Oleaginosas Anuales. - Instituto Colombiano Agropecuario, Palmira (Colombia) (Instituto Colombiano Agropecuario, 2018)
Fríjol-Phaseolus vulgaris